AUTOCORRELATION ANALYSIS OF CARDIOINTERVALOGRAMS IN THREE GROUPS OF PATIENTS WITH EXTENDED ANALYSIS OF PRIMARY DATA PROCESSING - Sakovich T. N. (Žurnal Grodnenskogo Gosudarstvennogo Medicinskogo Universiteta, 2020)
Purpose of the study. To develop a method for analyzing the seasonal and cyclic components of R-R intervals by estimating the autocorrelation function (ACF). Material and methods. The study consists of conducting a practical analysis of ACF as an application to R-R intervals, divided into three groups: all patients are patients with atrial fibrillation. The first group had tachycardia; the second had bradycardia; the third group - are patients without specific features. It should be noted that the age of the patients, according to which the analysis was carried out, is from 40 years and older. Results. The module developed at VBA (Visual Basic for Applications) enables to apply the methods of primary processing of the studied data, to create the ACF with its graphic representation for rather large values of the lag variable τ=1,100. Samples of 1000 values were examined. The most optimal data cleaning methods have been selected to get rid of excessive noise. A detailed analysis of ACF was carried out in the three groups of patients. Impressive research statistics have been compiled. Conclusions. In people with signs of tachycardia, all ACF ratios were not significant. In cases with severe tachycardia, ACF coefficients were positive, and had a decreasing trend. In the series with signs of bradycardia, almost all ACF coefficients were significant. ACF decreased with increasing lag τ. It can be concluded that in this group of time series there is a marked constant linear trend. In the group of patients with normal heart rate dynamics, insignificant ACF coefficients were obtained, which indicates the absence of any tendency. The coefficients were concentrated along the axis of the lag, had both positive and negative values. The oscillating process indicates only a strong stochastic component of the studied data.